Evaluasi Program Penguatan Karier Peserta Didik Melalui Layanan Bimbingan Karier di Sekolah Menengah Kejuruan - Indra Jasman; Ambiyar Ambiyar; Hasan Maksum (Education Achievement: Journal of Science and Research, 2026)
Career guidance services have become an essential component of vocational education in preparing students to successfully transition into employment, higher education, or entrepreneurship. Nevertheless, the implementation of career development programs in SMKN 2 Pariaman has not yet been fully optimized due to limited program evaluation, inadequate industry collaboration, and insufficient support for students' career planning and career adaptability. This study aimed to evaluate the effectiveness of the student career strengthening program delivered through career guidance services using the Context, Input, Process, Product (CIPP) evaluation model. A descriptive quantitative approach was employed at a public vocational high school involving twelfth-grade students who had participated in career guidance activities. The sample was determined using proportionate stratified random sampling, while data were collected through a validated and reliable questionnaire supported by document analysis. Descriptive statistical analysis, including mean, percentage, standard deviation, and frequency distribution, was conducted using IBM SPSS Statistics. The findings revealed that the overall implementation of the career strengthening program was categorized as good, achieving an average score of 3.95 (78.90%). Among the four evaluation components, Context obtained the highest score (83.60%), indicating that the program was well aligned with school policies and students' career development needs. Meanwhile, the Product component recorded the lowest score (75.80%), suggesting that students' career readiness, career decision-making, and career adaptability require further enhancement. The study concludes that the CIPP evaluation model provides a comprehensive framework for assessing career guidance programs and generates practical recommendations for improving career services through stronger industry partnerships, systematic career assessment, and technology-enhanced guidance practices, thereby supporting graduates' employability and lifelong career development.